Active surveillance for clinically localized renal tumors: An updated review of current indications and clinical outcomes. (17th March 2015) - Borghesi, Marco; Brunocilla, Eugenio; Volpe, Alessandro; Dababneh, Hussam; Pultrone, Cristian Vincenzo; Vagnoni, Valerio; La Manna, Gaetano; Porreca, Angelo; Martorana, Giuseppe; Schiavina, Riccardo
Abstract The widespread use of abdominal imaging has led to an increasing detection of small renal masses, and approximately 20–30% of those tumors will prove to be benign, with low metastatic potential if not immediately treated. In elderly or comorbid patients diagnosed with small renal masses, competing cause mortality seems to exceed cancer‐specific mortality at short‐ and intermediate‐term follow up. In these cases, surgery might represent an overtreatment, and an expectant management, such as active surveillance, might be proposed. According to the current available evidence, active surveillance is a safe and reasonable option for patients with renal tumors ≤4 cm (cT1a) and short life expectancy. A few studies with short‐term follow up reported the preliminary results of active surveillance even in cT1b–cT2 tumors, with acceptable risk of disease progression and mortality, even if this approach should be considered in this setting only for highly‐selected and well‐informed patients. Furthermore, surveillance protocols can be proposed in selected patients with uncomplicated benign tumors, such as angiomyolipomas, in which active surveillance should be considered the initial standard management. At present, reliable clinical predictors of a tumor's growth rate and aggressiveness are not available. Renal tumor biopsy is useful in the clinical work‐up of patients who are candidates for active surveillance, in order to improve patient selection based on tumor histological characterization. Despite the proof of safety offered by expectant management for small renal masses in selected patients, further prospective studies with longer follow up are required in order to confirm the indications and long‐term oncological outcomes of active surveillance protocols for renal tumors.